Bilateral patellar tendon repair with suture bridge augmentation: A case report - Brett Biedermann; Will Hill; William J. Karakash; Ioanna K. Bolia; George F. Rick Hatch, III (Trauma Case Reports)
We describe the case of a 37-year-old male who presented with simultaneous bilateral patellar tendon rupture without any associated risk factors. Additionally, this is the first reported use of the suture bridge technique with patellar and tibial suture anchors in repairing bilateral proximal patellar tendon rupture. At 12-month follow-up, the patient had normal alignment, no effusion, and symmetric quadriceps strength.